2014
DOI: 10.1111/1440-1681.12280
|View full text |Cite
|
Sign up to set email alerts
|

KCNJ11 E23K variant is associated with the therapeutic effect of sulphonylureas in Chinese type 2 diabetic patients

Abstract: The aim of the present study was to investigate the effect of the E23K variant of the potassium inwardly rectifying channel, subfamily J, member 11 (KCNJ11) gene on gliclazide modified release (MR) treatment in newly diagnosed patients with type 2 diabetes mellitus (T2DM). A total of 108 diabetic patients with no history of antidiabetic medication was treated with gliclazide MR for 16 weeks and underwent follow up at Weeks 2, 4, 8, 12 and 16. All patients were genotyped for KCNJ11 E23K (rs5219). At baseline, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 22 publications
(46 reference statements)
2
20
0
1
Order By: Relevance
“…Gliclazide MR initiates insulin secretion by closing potassium channels. Our previous research indicated that the KCNJ11 E23K variant is associated with the therapeutic effect of gliclazide in Chinese patients with T2DM [20] . However, the relationship between KCNQ1 and gliclazide has rarely been reported.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Gliclazide MR initiates insulin secretion by closing potassium channels. Our previous research indicated that the KCNJ11 E23K variant is associated with the therapeutic effect of gliclazide in Chinese patients with T2DM [20] . However, the relationship between KCNQ1 and gliclazide has rarely been reported.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, it has been reported recently that KCNQ1 rs2237897 is related to the efficacy of gliclazide monotherapy in Chinese patient who are newly diagnosed with type 2 diabetes [19] . Our previous pharmacogenetic study of gliclazide demonstrated that KCNJ11 E23K can influence responses to gliclazide due to its effect on insulin secretion in Chinese patients who are newly diagnosed with T2DM [20] . The potassium inwardly rectifying channel, subfamily J, member 11 (KCNJ11) gene is well known to encode a subunit of the inwardly rectifying potassium channel Kir6.2, which forms the K ATP channels in pancreatic β cells [20] .…”
Section: Abcc8 Kcnj11 Cyp2c9 Tcf7l2 Pparg Irs1 and Nos1apmentioning
confidence: 99%
See 3 more Smart Citations